Diabetic Retinopathy: Focus on Minority Populations - Arpine Barsegian; Boleslav Kotlyar; Justin Lee; Moro O Salifu; Samy I McFarlane (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2017)
Diabetic retinopathy is a major cause of blindness in the United States. With rise of the epidemic of obesity and diabetes in the USA and around the globe, serious and common diabetic complications are evolving as a major public health problem, particularly among minority populations. These populations are disproportionately affected by diabetes and 2-3 times more likely to develop visually signifi cant complications. In this highly illustrated review article, we discuss the diabetic epidemic, highlighting the biology and the pathophysiologic mechanisms of this disorder on the anatomy of the eye. We also discuss the risk factors and the implications for minority populations. For the health care providers, we provide cutting edge information and imminently relevant information to help evaluate, manage, and know when to refer their patients to a specialist in ophthalmology to quell the tide of the epidemic. Pubmed link: https://www.ncbi.nlm.nih.gov/pubmed/29756128